The structure of solutions of the matrix linear unilateral polynomial equation with two variables - Dzhaliuk, N.S.; Petrychkovych, V.M. (Carpathian Mathematical Publications, 2017)
We investigate the structure of solutions of the matrix linear polynomial equation A(λ)X(λ)+B(λ)Y(λ)=C(λ), in particular, possible degrees of the solutions. The solving of this equation is reduced to the solving of the equivalent matrix polynomial equation with matrix coefficients in triangular forms with invariant factors on the main diagonals, to which the matrices A (λ), B(λ) and C(λ) are reduced by means of semiscalar equivalent transformations. On the basis of it, we have pointed out the bounds of the degrees of the matrix polynomial equation solutions. Necessary and sufficient conditions for the uniqueness of a solution with a minimal degree are established. An effective method for constructing minimal degree solutions of the equations is suggested. In this article, unlike well-known results about the estimations of the degrees of the solutions of the matrix polynomial equations in which both matrix coefficients are regular or at least one of them is regular, we have considered the case when the matrix polynomial equation has arbitrary matrix coefficients A(λ) and B(λ).